Rationalisation of the activities of phenolic (vitamin E-type) antioxidants. Issue 4 (2003) - Rhodes Rhodes, Christopher J. Christopher J.; Tran Tran, Thuy T. Thuy T.; Denton Denton, Philip Philip; Morris Morris, Harry Harry
Abstract : Using Transition-State Theory, experimental rate constants, determined over a range of temperatures, for reactions of vitamin E type antioxidants are analysed in terms of their enthalpies and entropies of activation. It is further shown that computational methods may be employed to calculate enthalpies and entropies, and hence Gibbs Free Energies, for the overall reactions. Within the Linear Free Energy Relationship (LFER) assumption, that the Gibbs Free Energy of activation is proportional to the overall Gibbs Free Energy change for the reaction, it is possible to rationalise, and even to predict, the relative contributions of enthalpy and entropy for reactions of interest, involving potential antioxidants.